Antibacterial Photoactivity and Thermal Stability of Tetra‐cationic Porphyrins Immobilized on Cellulosic Fabrics. (29th November 2020) - Fayyaz, Fatemeh; Rassa, Mehdi; Rahimi, Rahmatollah
Abstract: The thermal stability and photo‐bactericidal effect of several tetra‐cationic porphyrins and their zinc ion compounds immobilized onto cellulosic fabrics against S. aureus, P. aeruginosa, and E. coli were investigated and compared using a 100 W tungsten lamp. Immobilization of various concentrations of these photosensitizers onto cellulosic fabrics was carried out and characterized by ATR‐FT‐IR, DRS, TGA, and SEM. Applied cellulosic fabrics with the photosensitizers exhibited remarkable photo‐stability, thermal stability, and antimicrobial activity against these studied strains. Abstract : Several tetra‐cationic porphyrins and their zinc ion compounds immobilized onto cellulosic fabrics. A 100 Watt tungsten lamp was used as light source in a shaking incubator. The thermal stability and photo‐bactericidal effect of these porphyrins were investigated against S. aureus, P. aeruginosa, and E. coli .